Constraints in the adoption of Indigenous farming practices - Kanagasabapathi, K; Sakthivel, V (Journal of Extension Education, 2017)
Indigenous farming is a production system, based on renewal of ecological processes and strengthening of ecological functions of farm ecosystem to produce safe, healthy and sustainable food. Indigenous agriculture is being adopted by the farmers of Kolli Hills in centre Tamil Nadu for different reasons. However, a lot of constraints prevent the farmers in adopting indigenous farming practices, that include poor yield, poor marketing facilities, higher production cost and urbanization